A pilot study of how the past, present, and future are represented in three-dimensional space - Yabe, Yoshiko; Yamada, Sachie (Frontiers in Psychology, 2023)
Numerous studies have shown that the representation of temporal concepts is associated with spatial features such as position and size. In a conventional task called “Circle Test (CT)”, participants are asked to express the relative importance of the past, present, and future and to demonstrate relationships among them by drawing three circles representing the past, present, and future. Studies on various participants, including refugees, patients living with serious illnesses, and adolescents, have used it to understand the temporal perspectives of different test takers. On the other hand, a number of studies have suggested that concepts of time are represented in three-dimensional (3D) space. It is expected that temporal concepts of the past, present, and future could be recorded using a 3D drawing task. Here we created a 3D version of CT (the “Sphere Test [ST]”) to investigate the sagittal representation of time and to record the relative time importance and relatedness allowing the shielding relationships and the laws of perspective. We conducted experiments with university students to compare the results from the CT and from the ST. Our results suggested that not all on-screen overlapping can be interpreted as representing a connection between two time zones in 3D space. We also found correlations between the chosen sizes of the three circles in the CT and ST —i.e., the on-screen sizes of the past and present circles were positively correlated. In contrast, we observed no correlation between the on-screen sizes of the future circles in the two tests. The alignment pattern along the sagittal axis showed different patterns from the horizontal and vertical axes. In conclusion, this study sheds new light on the third dimension of the spatial representation of time and may help us understand the relationship between temporal perspectives and other factors including mental health.